2010
DOI: 10.1128/aac.01808-09
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Gram-Negative Pathogens Isolated from Patients with Complicated Intra-Abdominal Infections in the United States, 2007-2008: Results of the Study for Monitoring Antimicrobial Resistance Trends (SMART)

Abstract: During 2007-2008, 1,036 Gram-negative bacilli were isolated from patients with complicated intra-abdominal infections in the United States. Against members of the family Enterobacteriaceae, the most active agents in vitro were ertapenem, imipenem, and amikacin, while the least active agent was ampicillin-sulbactam. Ertapenem and imipenem were active against all extended-spectrum-beta-lactamase (ESBL)-positive Escherichia coli. Antimicrobial resistance in Gram-negative bacilli isolated from patients with compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
21
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 12 publications
6
21
1
2
Order By: Relevance
“…However, ESBL-E are frequently susceptible to PTZ in many areas of the world. Our data among the patients treated empirically with PTZ and AMC are similar to the rates of suscep-tibility reported by other authors (frequently higher than 70% for PTZ [6][7][8][9][10] and higher than 60% for AMC [11,30]). Finally, these results encourage the further investigation of newer BLBLI combinations that are active even against some carbapenemase-producing Enterobacteriaceae.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, ESBL-E are frequently susceptible to PTZ in many areas of the world. Our data among the patients treated empirically with PTZ and AMC are similar to the rates of suscep-tibility reported by other authors (frequently higher than 70% for PTZ [6][7][8][9][10] and higher than 60% for AMC [11,30]). Finally, these results encourage the further investigation of newer BLBLI combinations that are active even against some carbapenemase-producing Enterobacteriaceae.…”
Section: Discussionsupporting
confidence: 78%
“…Although hyperproduction of ␤-lactamases or additional resistance mechanisms may hamper the activity of these compounds, ␤-lactam/␤-lactamase inhibitor combinations (BLBLIs) such as amoxicillin-clavulanate (AMC) or piperacillin-tazobactam (PTZ) remain active against a considerable proportion of ESBL-E in many areas of the world (6)(7)(8)(9)(10)(11). However, the efficacy of BLBLIs for treating serious infections caused by ESBL-E is controversial (11)(12)(13).…”
mentioning
confidence: 99%
“…In this study, the most common baseline pathogens were Escherichia coli, Klebsiella spp., streptococci, enterococci, and Bacteroides spp., consistent with those associated typically with cIAI, although the recovery of anaerobic pathogens was lower in the present study than in some recent reports (20,21). These pathogens were eradicated at similar rates by both study drugs.…”
Section: Discussioncontrasting
confidence: 33%
“…A total of 3,160 clinical isolates of Escherichia coli from IAIs during 2008 and 2009 from 13 European countries were evaluated, and 11% were found to produce extended-spectrum ␤-lactamases (ESBLs) (107). The SMART report for 2008 U.S. E. coli strains from IAIs indicated that about 4.7% of strains produced ESBLs (113). Emphasizing the importance of geographic trends, the rate of ESBL-producing E. coli strains from the Asia-Pacific region was 36.8% using SMART data from this region (47).…”
Section: Intra-abdominal Infectionsmentioning
confidence: 99%